Isolation and screening of protease producing halotolerant bacteria from fermented freshwater fishes - Bandavong, Viraxay; Unban, Kridsada; Kanpiengjai, Apinan; Khanongnuch, Chartchai (Food and Applied Bioscience Journal, 2017)
A total of 45 halotolerant bacterial isolates were isolated from 38 samples of fermented freshwater fishes using modified MRS agar containing 20% (w/v) NaCl. Screening for protease production on modified MRS agar supplemented with 20% (w/v) NaCl and 0.5% (w/v) casein found that only 8 bacterial isolates formed clear zone and the isolates VK31 formed the widest clear zone following by isolate VK20. Confirmation of protease production in liquid culture found that the enzyme activities produced by both isolates were found 4.41±0.02 and 3.35±0.04 U/mL, respectively. Based on the 16S DNA nucleotide sequence analysis, the isolate VK20 and VK31 were identified to be Virgibacillus halodenitrificans VK20 and Kushneria avicenniae VK31, respectively. Time course of protease production at 37oC for 3 days showed the maximum protease activity of 5.42±0.02 and 4.19±0.03 U/mL by V. halodenitrificans VK20 and K. avicenniae VK31, respectively.